2020
DOI: 10.3390/molecules25081874
|View full text |Cite
|
Sign up to set email alerts
|

First Example of Catalytic Synthesis of Cyclic S-Containing Di- and Triperoxides

Abstract: An efficient method for the synthesis of tetraoxathiaspiroalkanes, tetraoxathiocanes, and hexaoxathiadispiroalkanes was developed by reactions of pentaoxacanes, pentaoxaspiroalkanes, and heptaoxadispiroalkanes with hydrogen sulfide in the presence of a catalyst, Sm(NO3)3·6H2O. We found that the synthesized S-containing di- and triperoxides exhibit high cytotoxic activity against Jurkat, K562, U937, and HL60 tumor cultures, and fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The 1 H and 13 C NMR spectra of the isolated 11-(4-nitrophenyl)-2,3,5,6-tetraoxa-11-azaspiro­[bicyclo[5.3.1]­undecane-4,1′-cyclopentane] exhibit two sets of signals considerably differing in intensity (9:1). Indeed, bicyclic aza-peroxides of this class, like other diperoxides, , exist in solutions as equilibrium mixtures of conformers, which is due to high inversion barriers of the heterocycle. The major component of the mixture corresponds to conformer A ( 6a ) (Figure ), which is energetically the most favorable and occurs in the crystalline state (Table SI-5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1 H and 13 C NMR spectra of the isolated 11-(4-nitrophenyl)-2,3,5,6-tetraoxa-11-azaspiro­[bicyclo[5.3.1]­undecane-4,1′-cyclopentane] exhibit two sets of signals considerably differing in intensity (9:1). Indeed, bicyclic aza-peroxides of this class, like other diperoxides, , exist in solutions as equilibrium mixtures of conformers, which is due to high inversion barriers of the heterocycle. The major component of the mixture corresponds to conformer A ( 6a ) (Figure ), which is energetically the most favorable and occurs in the crystalline state (Table SI-5).…”
Section: Resultsmentioning
confidence: 99%
“…15 The presence of a heteroatom-containing peroxide moiety in antimalarial agents and in natural compounds such as artemisinin, verruculogen, and dioxetanone stimulates the research aimed at the development of synthetic routes to new heteroatomcontaining peroxide derivatives (Figure 1). In addition, high cytotoxic activities were found for dimeric diaza-hexaperoxides, 16 S-containing di-and triperoxides, 17 benzannulated di-and triperoxides, 18 tetraoxaspirododecanediamines, and tetraoxazaspirobicycloalkanes. 19 There is evidence of a high cytotoxic activity of natural heteroatom-containing cyclic compounds with a heteroatom (oxygen and nitrogen atom) in the α-position to the peroxide group, such as 11-aza-artemisinin, 6-azaartemisinin, and catharoseumine (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Using modern cell technologies, we have found that the newly synthesized 3,6‐di(spirocycloalkane)‐substituted 1,2,4,5,7,8,10‐heptaoxacycloundecanes, α,ω‐di(1,2,4,5,7,8‐hexaoxa‐10‐azacycloundecan‐10‐yl)alkanes, N ‐substituted hexaoxazadispiroalkanes, macrocyclic aza(diaza)‐triperoxides, and hexaoxazadispiroalkane‐substituted amines have a high cytotoxic activity against Jurkat, K562, U937, and HL60 tumor cells. Furthermore, these peroxide classes induce apoptosis and arrest the cell cycle by affecting all of its phases [29–32] …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these peroxide classes induce apoptosis and arrest the cell cycle by affecting all of its phases. [29][30][31][32] Thus, wide use of natural and synthetic O-, N-, and Scontaining cyclic and acyclic peroxides as pharmaceutical drugs stimulates the development of effective and convenient methods for the preparation of new classes of heteroatomcontaining peroxides, especially N-containing ones, which are of exceptional interest for the design of innovative drugs for the treatment of cancer in humans. [33][34][35] Before our studies, no data on the synthesis of saturated heteroatomic macrocyclic peroxides (eight or more atoms in the ring) with two or three peroxide groups in the ring were reported in the world literature.…”
Section: Introductionmentioning
confidence: 99%